2016
DOI: 10.1177/0962280214529104
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate tests based on interpoint distances with application to magnetic resonance imaging

Abstract: The multivariate location problem is addressed. The most familiar method to address the problem is the Hotelling test. When the hypothesis of normal distributions holds, the Hotelling test is optimal. Unfortunately, in practice the distributions underlying the samples are generally unknown and without assuming normality the finite sample unbiasedness of the Hotelling test is not guaranteed. Moreover, high-dimensional data are increasingly encountered when analyzing medical and biological problems, and in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Type I error rate and power were estimated based on 1,000 randomly selected data sets from each distribution, for each setting of sample sizes and scale parameter patterns. Marozzi (2016) suggested that only 253 random permutations are necessary with 1,000 random data sets if the goal of the simulation is to estimate the power of a test and only a "rough" estimate of the permutation p-value is required, while Keller-McNulty and Higgins (1987) recommended a random sample of at least 1,600 permutations to estimate the exact p-value for a permutation test. Since precise estimation of the permutation test p-values was considered important, a conservative 2,000 random permutations was utilized.…”
Section: Distributionsmentioning
confidence: 99%
“…Type I error rate and power were estimated based on 1,000 randomly selected data sets from each distribution, for each setting of sample sizes and scale parameter patterns. Marozzi (2016) suggested that only 253 random permutations are necessary with 1,000 random data sets if the goal of the simulation is to estimate the power of a test and only a "rough" estimate of the permutation p-value is required, while Keller-McNulty and Higgins (1987) recommended a random sample of at least 1,600 permutations to estimate the exact p-value for a permutation test. Since precise estimation of the permutation test p-values was considered important, a conservative 2,000 random permutations was utilized.…”
Section: Distributionsmentioning
confidence: 99%
“…, we obtain a test that has asymptotically level α. This gives an alternative to the classical Hotelling test, which is not well suited for the high dimensional setup, see Marozzi [28].…”
Section: Central Limit Theorem For Hilbert Space-valued Functionals Omentioning
confidence: 99%
“…Berrendero, Cuevas, and Pateiro-López (2016) identify a shape with the corresponding IPD distribution. Marozzi (2015Marozzi ( , 2016 discusses multivariate tests based on IPDs for high dimensional low sample size data and applies them to magnetic resonance images. Baringhaus & Franz (2004), Rosenbaum (2005) and Jurecková & Kalina (2012) utilise IPDs to construct tests for the general two-sample problem.…”
Section: Introductionmentioning
confidence: 99%